Diurnal modulation of visual motion prediction. (August 2015) - Takao, Motoharu; Miyajima, Hiroaki; Shinagawa, Takanori
<x xml:space="preserve">Abstract</x> Predicting the future position of moving objects is an essential cognitive function used for many daily activities, such as driving, walking and reaching. The experiments described in this paper show a marked diurnal modulation of motion prediction in inflating image perception. This motion prediction was shown to be more accurate in the afternoon than in the morning. In contrast, such modulation could not be found in deflating image perception. Such diurnal fluctuations may be mediated by circadian properties of retinal cone photoreceptors.